Life narratives of cancer patients under palliative care: the look of poetic pieces (Research, Society and Development, 2021)
Introduction: Total pain in palliative care implies attention to the biopsychosocial and spiritual dimensions of each person. The pain of someone with incurable cancer transcends their physical pain. Getting to know a person beyond their illness, illuminating their subjectivities, can tone up more humanized behaviors and a favor of a doctor-patient relationship that will benefit from the enhancement of empathy on the part of the doctor. Objective: to present poetic pieces about the most valuable aspects of the life of cancer patients under palliative care, based on life narratives. Method: this is a qualitative, prospective, exploratory study, based on the methodology of oral narratives of life histories of cancer patients enrolled in the Palliative Care clinic of the Oncology Center in the city of São Caetano do Sul. The clinic was renamed Extended Anamnesis, and two interviews were collected: the first, where the respondent was instigated to produce a life report from childhood until before the symptoms of the disease. In the second, the patient was introduced to a renowned artistic work and discussed the effect that the work had on him. Results: the narratives made it possible to understand aspects that are inaccessible to traditional assessment, bringing the doctor and the patient closer together, promoting a comprehensive and empathetic approach proposed by the principles of palliative care. Conclusion: inspired poetic pieces can foster the empathetic look of professionals who treat cancer patients undergoing palliation, as well as students, who initiate contact with the practice of humanized medicine.